1999
DOI: 10.1046/j.1365-3059.1999.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Indian peanut clump virus (IPCV) infection on wheat and barley: symptoms, yield loss and transmission through seed

Abstract: Wheat and barley crops were shown to be susceptible to Indian peanut clump virus (IPCV) under field conditions. In wheat, the Hyderabad isolate of IPCV (IPCV-H) induced symptoms resembling the rosette caused by soil-borne wheat mosaic virus, and these were apparent only three weeks after emergence. Early-infected plants were severely stunted and dark green, with chlorotic streaks on the youngest leaves, which turned necrotic as the plants aged; most of these plants died. Late-infected plants were also stunted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Fungi cultured on artificial medium were tested at a dilution of 25 µg/ml and mixed with dried healthy sorghum root (75 µg/ml) to approximate the amount of P. graminis sporosori in infected sorghum roots. b * = Single-sporosorus cultures I 1-1 , I [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , and I 1-229 derived from the isolate I 1 . c Mean absorbance readings at 405 nm as the percentage of that observed for the homologous antigen P. graminis from India isolate I 1 .…”
Section: Production Of Antiserummentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi cultured on artificial medium were tested at a dilution of 25 µg/ml and mixed with dried healthy sorghum root (75 µg/ml) to approximate the amount of P. graminis sporosori in infected sorghum roots. b * = Single-sporosorus cultures I 1-1 , I [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , and I 1-229 derived from the isolate I 1 . c Mean absorbance readings at 405 nm as the percentage of that observed for the homologous antigen P. graminis from India isolate I 1 .…”
Section: Production Of Antiserummentioning
confidence: 99%
“…They transmit at least 12 different plant viruses in the genera Benyvirus, Bymovirus, Furovirus, and Pecluvirus (1,30,32). Peanut clump virus (PCV) and Indian peanut clump virus (IPCV) are members of the genus Pecluvirus (40) that affect the production of peanut and monocotyledonous crops in West Africa and in the Indian subcontinent (3,9,40,43). In the absence of cost-effective methods for the management of peanut clump disease (40), it was essential to study its epidemiology with emphasis on identification of the hosts for the virus and P. graminis and their influence on the perpetuation and spread of clump disease.…”
Section: Introductionmentioning
confidence: 99%
“…Muszelka were soaked in distilled water on a thin layer of cotton in Petri dishes (20 cm in diameter) and left for 4 days for germination at room temperature. Before germination the seeds were washed with 0.026 M Na 3 PO 4 for 10 min to remove any virus capsid from the surface of the seeds (Delfosse et al 1999). Four-day-old whole seedlings (leaves and roots) were taken for diagnostics.…”
Section: Methodsmentioning
confidence: 99%
“…Tanker and Equinox were collected from crops grown on land containing a natural inoculum source of SBCMV in 2001(Budge et al 2003. For direct seed testing, triplicate batches of 20 seed from each cultivar were washed with 0.026 M Na 3 PO 4 : 12 H 2 0 for 10 min to remove any virus capsid from the surface of the seed (Delfosse et al 1999). RNA was extracted using a MagExtractor® Total RNA purification kit (ThermoLabsystems) in combination with a Kingfisher ml magnetic particle separator (ThermoLabsystems) following manufacturer's protocol (Toyobo, Japan).…”
mentioning
confidence: 99%
“…However, severe symptoms were evident in the crop from which the seed was harvested, as early as January during the 2001-2002 season (Budge et al 2003). Studies of the inoculum dynamics of Indian peanut clump virus (IPCV) have shown early infection strongly correlates with increases in true seed transmission (Delfosse et al 2002), indeed IPCV has been shown to be seedtransmitted in wheat at 0.5-1.3% (Delfosse et al 1999). Work in Poland identified SBCMV virus particles in the mesophyll cells of rye seeds, suggesting the virus was transmitted at a rate of 3% in rye seed (Garbaczewska et al 1997;Jezewska 1995).…”
mentioning
confidence: 99%